Parallel algorithms in computational science - Heermann, Dieter W.; Burkitt, Anthony N. (Springer, 1991)
1. Introduction -- 2. Computer Simulation Methods -- 2.1 Essential Features of Simulation Methods -- 2.2 The Monte Carlo Algorithm -- 2.3 Molecular Dynamics -- 2.4 Hybrid Molecular Dynamics -- 2.5 Accuracy Considerations and Finite-Size Problems -- 2.6 Monte Carlo Algorithm for the Ising Model -- 3. Physics and Parallelism -- 4. Concepts of Parallelism -- 4.1 Some Basic Definitions -- 4.2 The Complexity of Computation -- 4.3 More on Models and Methods -- 4.4 Performance Measurements -- 5. Parallel Machines and Languages -- 5.1 General Purpose Parallel Computers -- 5.2 Parallel Machines for Special Physics Problems -- 5.3 Languages for Parallel Computers -- 5.4 The Matching Problem -- 6. Replication Algorithms -- 7. Geometrically Parallel Algorithms -- 7.1 Geometric Parallelization -- 7.2 Strips, Squares and Checker-Boards -- 7.3 Non-local and Cluster Algorithms -- 7.4 Parallel Molecular Dynamics Algorithms -- 7.5 Hybrid Molecular Dynamics -- 7.6 Polymers on the Lattice -- 7.7 Off-Lattice Polymers -- 7.8 Hybrid Molecular Dynamics for Polymers -- 7.9 Limits of Geometric Parallelization -- 8. Data Parallel Algorithms -- 8.1 Data Parallel Algorithm for Long-Range Interactions -- 8.2 Polymers -- 9. Introduction to a Parallel Language -- 9.1 Transputer-Based Parallel Machines -- 9.2 Parallel Programming in Occam -- Appendices -- A. A Parallel Ising Model Program -- B. Random Number Generator -- C. A Parallel Molecular Dynamics Program -- References
Keywords: Paralleler Algorithmus; Computersimulation